Nanometric cutting: Mechanisms, practices and future perspectives. (July 2022) - Fang, Fengzhou; Lai, Min; Wang, Jinshi; Luo, Xichun; Yan, Jiwang; Yan, Yongda
Abstract: Nanometric cutting removes material at nanoscale and generates high-quality surfaces with a nanometric finish. In past decades, it has thrived as a mainstream manufacturing technology to produce critical components to advance scientific discovery and promote innovation in various fields, such as astronomy, aerospace, microelectronics, optics and photonics, biology and quantum technology. Therefore, it is timely to develop a review article capturing such developments and establishing directions for future advancement. This article systematically reviews the fundamental issues such as cutting model, material deformation mechanism and tool wear in nanometric cutting. It also presents the working principles of innovative ion implantation-assisted, laser-assisted and ultrasonic vibration-assisted nanometric cutting methods to overcome the challenges of machining difficult-to-cut materials. Practical techniques for the generation of high-quality complex or structured surfaces are also discussed. Finally, challenges and future perspectives of nanometric cutting, as well as the evolution towards atomic and close-to-atomic scale manufacturing, are outlined. Graphical abstract: Image 1 Highlights: Fundamental studies on nanometric cutting are comprehensively reviewed. Critical topics on principle, modeling and experimental technology are presented. Specific methods for difficult-to-cut materials are discussed. Nanometric cutting practice and typical applications are presented. Challenges and future perspectives of nanometric cutting are outlined.